STERIC EFFECT IN DIFLUORINEALCANE MOLECULES - A.V. Kotomkin; N.P. Rusakova; V.V. Turovtsev; Yu.D. Orlov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2019)
Fifteen conformers of the CHF2 – (CH2)6 – CH3 molecule were found. Within a «quantum theory of atoms in molecules», their equilibrium geometry, total energies and the electron structure were studied. Analysis and comparison of electron parameters revealed in some structures a steric effect from CHF2.